KANDUNGAN FOSFOR DAN KALSIUM DAGING AKIBAT PEMBERIAN TAMBAHAN KUNYIT JAHE DAN SALAM PADA RANSUM BEBEK The Content Of Phosphorus And Calcium Meat Due To The Addition Of Turmeric Ginger And Greetings On The Duck Rataion - Mei - Sulistyoningsih; Renni - Rakhmawati; Wonaerika - Ayu (Jurnal Pangan dan Gizi, 2017)
This study aims to determine the content of phosphorus and calcium meat due to the addition of turmeric, ginger, greetings on duck rations. Subjects used in the study were 100 DOD unsex until 8 weeks of data collection. This study used a Completely Randomized Complete Randomized Design (RAL) design, with four treatments and four replications. The treatments in this study were P1 = organic feed (control), P2 = organic feed + turmeric 0.2%, P3 = organic feed + ginger 2%, P4 = organic feed + bay leaf 3%. Research variables measured were phosphorus content and calcium content in duck meat. The data obtained are then analyzed using the variance (ANOVA). The results of this study showed no effect of additional provision of turmeric, ginger, greetings to the content of phosphorus and duck meat calcium (P>0,05). Keywords: turmeric, ginger, greetings, phosphorus, calcium, duck meat